2010
DOI: 10.1002/ijc.25242
|View full text |Cite
|
Sign up to set email alerts
|

Check your cultures! A list of cross‐contaminated or misidentified cell lines

Abstract: Continuous cell lines consist of cultured cells derived from a specific donor and tissue of origin that have acquired the ability to proliferate indefinitely. These cell lines are well‐recognized models for the study of health and disease, particularly for cancer. However, there are cautions to be aware of when using continuous cell lines, including the possibility of contamination, in which a foreign cell line or microorganism is introduced without the handler's knowledge. Cross‐contamination, in which the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
385
1
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(397 citation statements)
references
References 52 publications
3
385
1
8
Order By: Relevance
“…Standardized PCR-based methods are now available for authenticating cell lines by reference to an interactive cell line database (www.dsmz.de/services/services-human-and-animalcell-lines/online-str-analysis.html), although continually updated lists of false examples are published (5). It is now up to journals and grant agencies to encourage full exploitation of these resources.…”
mentioning
confidence: 99%
“…Standardized PCR-based methods are now available for authenticating cell lines by reference to an interactive cell line database (www.dsmz.de/services/services-human-and-animalcell-lines/online-str-analysis.html), although continually updated lists of false examples are published (5). It is now up to journals and grant agencies to encourage full exploitation of these resources.…”
mentioning
confidence: 99%
“…This cell line has revealed much efficiency and stability in extrinsic gene transfection (13)(14)(15); in this study, we selected the cell line as the host cell and conducted the human CD14 gene transfection into it.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies over the past decade have demonstrated the problem of cell line contamination which generally arises due to poor laboratory practice (Capes-Davis et al 2010). Reported reasons include cell spreading via aerosols, use of unplugged pipettes, sharing media/reagents between cell lines and the use of mitotically inactivated feeder cells or conditioned medium, which have not had originating cells removed (van Pelt et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These continuous cell lines are repeatedly passaged, reliably cryopreserved and retain representative properties of the cells and tissues from which they were derived. These attributes have resulted in cell lines being widely used as model systems for the study of cellular processes in health and disease and are therefore commonly used within biomedical research and the pharmaceutical industry (Capes-Davis et al 2010). Recently the robustness of cell cultures used in research has been under scrutiny as data have demonstrated that cross-contamination with other cells lines, misidentification of cell lines, and the use of cultures at high passage numbers has resulted in the generation of erroneous results (Hughes et al 2007).…”
Section: Introductionmentioning
confidence: 99%